Islamic Corporate Governance, Financial Leverage dan Kinerja Keuangan: Volume Pembiayaan Sebagai Pemoderasi - Ma'wa, Muhammad Agus Futuhul Ma'wa; Siregar, Suci Wulandari Siregar; Indarningsih, Nur Aisyah Indarningsih (Mutanaqishah: Journal of Islamic Banking, 2023)
This investigation seeks to provide factual evidence of the financial performance of Islamic commercial banks (BUS). The dependent variable of this research is the financial performance which is evaluated by Return On Assets (ROA). In this study, Islamic Corporate Governance and Financial Leverage on Financing Volume are independent factors used as moderating variables. This study, the population were twelve Islamic Commercial Banks (BUS) registered at Bank Indonesia. Based on a randomly selected sampling technique, research information is extracted from the 2016-2021 annual financial statements. Because the data consists of time series and cross-sectional information, the Eviews 12 program is used to perform panel data regression analysis. The results showed that Islamic Corporate Governance (ICG) with the indicator of the Number of Sharia Audit Committees had a significant positive effect on financial performance. Financial Leverage as a proxy for DER has no effect on financial performance. For the moderating variable in this study, namely the volume of financing preceded by FDR, it cannot moderate the financial performance of Islamic commercial banks in Indonesia for the 2016-2021 period.